Pore-filled film, fuel cell, and electrolysis device

By filling the pores of the pores of the pores of the porous substrate with specific structures, the problem of insufficient mechanical strength and durability of the polymer film is solved, and the improvement of chemical durability and mechanical strength is achieved. It is suitable for high-performance fuels Battery and electrolytic devices.

CN119301780APending Publication Date: 2025-01-10INSTITUTE OF SCIENCE TOKYO +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380041549.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-19
Filing Date
2023-05-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing polymer films have shortcomings in terms of mechanical strength and durability, especially in the long-term use, which is difficult to meet the needs of fuel cells and electrolytic devices.

Method used

Polyary substrates are used to fill polyarylene polymers, and the chemical durability and mechanical strength of the film are enhanced by filling the pores of the pores of the pores of the pores, and the polyarylene polymers with specific structural units.

Benefits of technology

It achieves significant improvements in chemical durability and mechanical strength, provides a fine-pore filling film with excellent durability, suitable for fuel cells and electrolytic devices, and improves ion conductivity and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301780A_ABST
    Figure CN119301780A_ABST
Patent Text Reader

Abstract

Provided are: a pore-filled film having excellent chemical durability and mechanical strength; and a fuel cell and an electrolysis device which are provided with the pore-filled film and have excellent durability. The pore-filled film has a porous base material and a polyarylene polymer, and the pores of the porous base material are filled with the polyarylene polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a pore-filling membrane, a fuel cell, and an electrolysis device. Background Art

[0002] Electrolyte membranes are used in various fuel cells such as solid polymer fuel cells and solid alkaline fuel cells, or various electrolysis technologies such as water electrolysis. The electrolyte membranes are required to have excellent ion conductivity and durability that can withstand long-term use.

[0003] As a polymer having excellent chemical durability and ion conductivity, the present inventors have disclosed a specific polymer having no ether oxygen atom in the main chain skeleton (for example, Patent Documents 1 and 2).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-135487

[0007] Patent Document 2: Japanese Patent Application Publication No. 2021-42351 Summary of the invention

[0008] Problems to be Solved by the Invention

[0009] The polymers of Patent Documents 1 and 2 can be formed into films and used as electrolyte membranes. However, the mechanical strength of the polymer films is sometimes insufficient.

[0010] An object of the present disclosure is to provide a pore-filling membrane having excellent chemical durability and mechanical strength, and a fuel cell and an electrolysis device having excellent durability and including the pore-filling membrane.

[0011] Means of solving problems

[0012] The pore-filling membrane according to the present disclosure is characterized by comprising a porous substrate and a polyarylene polymer, wherein the polyarylene polymer is filled in the pores of the porous substrate.

[0013] In one embodiment of the pore-filled film, the polyarylene polymer has a structural unit represented by the following general formula (1).

[0014]

Chemical formula 1

[0015]

[0016] in,

[0017] Ar 1 It is an aromatic group having an ion exchange group, or a group formed by connecting aromatic rings having an ion exchange group through a single bond.1 Can be the same or different,

[0018] Ar 2 is an aromatic group having no ion exchange group, or a group in which two or more aromatic rings having no ion exchange group are connected by a single bond or a spiro atom, and a plurality of Ar 2 Can be the same or different,

[0019] Ar 1 The aromatic ring and Ar 2 The aromatic rings are connected by single bonds.

[0020] In one embodiment of the pore-filled film, the porous substrate is a polyolefin-based porous substrate.

[0021] In one embodiment of the pore-filled membrane, the polyolefin-based porous substrate is a polyethylene porous substrate, a polypropylene porous substrate, or a polytetrafluoroethylene porous substrate.

[0022] In addition, the present disclosure provides a fuel cell and an electrolysis device including the pore-filling membrane.

[0023] Effects of the Invention

[0024] According to the present invention, there are provided a pore-filling membrane having excellent chemical durability and mechanical strength, and a fuel cell and an electrolysis device having excellent durability and including the pore-filling membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic cross-sectional view showing an example of the main parts of the electrolysis device.

[0026] Figure 2 This is a schematic cross-sectional view showing an example of an anode catalyst.

[0027] Figure 3 This is a schematic cross-sectional view showing an example of an anode catalyst.

[0028] Figure 4 This is a schematic cross-sectional view showing an example of a cathode catalyst.

[0029] Figure 5 This is a schematic cross-sectional view showing an example of a main part of a fuel cell.

[0030] Figure 6 3 is a graph showing the results of the water electrolysis test of Example 1.

[0031] Fig. 7A This is a Raman spectrum of the interior of the pore-filling film of Example 1, etc.

[0032] Figure 7BThis is the Raman spectrum inside the pore-filling film of Example 1. DETAILED DESCRIPTION

[0033] Hereinafter, the pore-filling membrane, the fuel cell, and the electrolysis device will be described.

[0034] It should be noted that, in the present disclosure, unless otherwise specified, "polymer" includes "copolymer".

[0035] In the present disclosure, an “ion exchange group” refers to a functional group that has dissociative properties and is capable of performing ion exchange.

[0036] In addition, in the present disclosure, unless otherwise specified, "to" indicating a numerical range means that the numerical values ​​described before and after it as the lower limit value and the upper limit value are included.

[0037] For the purpose of clear explanation, the following description and drawings are appropriately simplified. In addition, in this specification, matters necessary for implementation that are not particularly mentioned can be understood as design matters for those skilled in the art based on the prior art in the field.

[0038]

Pore filling film

[0039] The pore-filled membrane disclosed herein is characterized by comprising a porous substrate and a polyarylene polymer, wherein the polyarylene polymer is filled in the pores of the porous substrate. With such a structure, mechanical strength can be imparted to the polyarylene polymer having excellent chemical durability.

[0040] <Porous substrate>

[0041] The porous substrate used for the present pore-filled membrane is a substrate having pores capable of retaining the polyarylene polymer. In view of improving ion conductivity, it is preferred that at least a part of the pores of the porous substrate be through-holes.

[0042] From the viewpoint of imparting mechanical strength, the substrate is preferably in the form of a nonwoven fabric or a porous film, and more preferably in the form of a porous film.

[0043] From the viewpoint of achieving both mechanical strength and ion conductivity, the porosity of the porous substrate (=volumetric volume of voids / bulk volume×100(%)) is preferably 30 to 95%, more preferably 40 to 80%, and even more preferably 45 to 70%.

[0044] From the viewpoint of achieving both mechanical strength and ion conductivity, the thickness of the porous substrate is preferably 5 to 200 μm, more preferably 7 to 100 μm, and even more preferably 10 to 50 μm.

[0045] In addition, from the viewpoint of filling and holding the polyarylene polymer and mechanical strength, the pore size of the porous substrate is preferably 10 to 10000 nm in average diameter, and more preferably 10 to 1000 nm.

[0046] From the perspective of chemical durability, particularly stability in alkali, the material of the porous substrate is preferably a polyolefin-based porous substrate. In addition, by using a polyolefin-based porous substrate, it is also possible to easily fill the polyarylene polymer with a weight average molecular weight of more than 100,000 high molecular weight polyarylene polymer. As a polyolefin-based porous substrate, from the perspective of mechanical strength and chemical resistance, preferably a polyethylene porous substrate, a polypropylene porous substrate or a polytetrafluoroethylene porous substrate. In addition, in the polyethylene porous substrate, preferably an ultra-high molecular weight polyethylene (for example, a weight average molecular weight of more than 1,000,000) porous substrate.

[0047] <Polyarylene polymer>

[0048] The present pore-filled film uses a polyarylene polymer as a filling polymer. By using a polyarylene polymer, a pore-filled film having excellent chemical durability can be obtained.

[0049] From the viewpoint of imparting excellent ion conductivity to the pore-filling membrane, the polyarylene polymer is preferably a polymer having a structural unit represented by the following general formula (1) (hereinafter also referred to as polymer (A)).

[0050]

Chemical formula 2

[0051]

[0052] in,

[0053] Ar 1 It is an aromatic group having an ion exchange group, or a group formed by connecting aromatic rings having an ion exchange group through a single bond. 1 Can be the same or different,

[0054] Ar 2 is an aromatic group having no ion exchange group, or a group in which two or more aromatic rings having no ion exchange group are connected by a single bond or a spiro atom, and a plurality of Ar 2 Can be the same or different,

[0055] Ar 1 The aromatic ring and Ar 2 The aromatic rings are connected by single bonds.

[0056] The polymer (A) is a polymer having two or more of the above structural units (1), having Ar 1 with Ar 2Alternating configuration structure, Ar 1 With ion exchange groups, Ar 2 It does not have ion exchange groups. 1 The aromatic groups and Ar 2 The aromatic groups are connected by single bonds to form the main chain. There are no ether oxygen (-O-), sulfonyl (-S(=O)2-), or carbonyl (-C(=O)-) skeletons in the main chain skeleton, and the chemical durability, especially the alkali durability, is excellent. It should be noted that the aromatic ring here refers to the aromatic ring constituting the main chain, and the aromatic ring constituting the main chain may also have an aromatic ring as a substituent. The aromatic ring constituting the main chain and the aromatic ring as a substituent (side chain) are distinguished.

[0057] Ar 1 It is an aromatic group having an ion exchange group, or a group in which aromatic rings having an ion exchange group are connected by a single bond. It should be noted that the ion exchange group refers to a functional group that has dissociative properties and can perform ion exchange.

[0058] When proton conductivity is imparted to the polymer (A), the ion exchange group is preferably an acidic group, wherein the acidic group is preferably a sulfonic acid group (-SO3H group), a phosphoric acid group (-H2PO4 group), or a carboxylic acid group (-COOH group), and more preferably a sulfonic acid group. It should be noted that the H of the above acidic group may be dissociated or may be replaced by an alkali metal ion, an alkaline earth metal ion, or the like.

[0059] In addition, when the polymer (A) is endowed with anionic conductivity, the ion exchange group is preferably a quaternary ammonium group or an imidazolium group, more preferably a quaternary ammonium group. From the perspective of alkali durability, the quaternary ammonium group is more preferably a quaternary alkylammonium group. It should be noted that the quaternary alkylammonium group includes a group in which an alkyl group bonded to a nitrogen atom is bonded to each other to form a ring structure, for example, it may be an azaadamantyl group, a quinuclidine group, etc.

[0060] Preferred specific examples of the quaternary ammonium group include groups represented by the following formulae (e-1) to (e-8). Preferred specific examples of the imidazolium group include groups represented by the following formula (f-1), and groups represented by the following formula (f-2) or groups represented by the following formula (f-3) are preferred.

[0061]

Chemical formula 3

[0062]

[0063] In the formula, R e Each independently represents a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, R fare each independently a hydrogen atom, a linear or branched alkyl group having 1 to 4 carbon atoms, or an aromatic group which may have a substituent, - For anions with a valence of 1 or more than 2, when there are multiple R e or R f When the multiple R e or R f It should be noted that the wavy line in the formula represents the same as the 1 A bond that is bonded to the aromatic ring side of the main chain.

[0064] As the above R e Specific examples of the alkyl group include methyl, ethyl, propyl, butyl, pentyl, hexyl, and cyclohexyl. f Specific examples of the alkyl group in R include methyl, ethyl, propyl, butyl, etc. f Examples of the aromatic group include a phenyl group, and examples of the substituent of the phenyl group include an alkyl group having 1 to 6 carbon atoms.

[0065] As the above A - , preferably inorganic anions, such as chloride ions (Cl - ), bromide ion (Br - ), iodide ion (I - ), bicarbonate ion (HCO3 - ), carbonate ions (CO3 - ), hydroxide ion (OH - )wait.

[0066] The above ion exchange groups can directly react with the Ar 1 In the embodiment of the present invention, the aromatic ring of the main chain of the polymer (A) is combined, and a linking group can also be provided, which can be combined with the aromatic ring constituting the main chain by the linking group. Wherein, the linking group represents an organic group that connects the acidic group, quaternary ammonium group or imidazolium group possessed by the ion exchange group to the aromatic ring constituting the main chain. As the organic group, a linear or branched alkylene group is preferred, wherein a linear alkylene group is preferred. The carbon number of the alkylene group can be appropriately adjusted according to the physical properties required for the polymer (A). For example, by setting the carbon number of the alkylene group to less than 20, preferably to less than 16, more preferably to less than 12, so that the ion exchange group capacity of the polymer (A) is increased. On the other hand, by setting the carbon number of the alkylene group to more than 2, preferably to more than 4, more preferably to more than 6, so that solubility and anti-swelling properties are excellent, so that the polymer (A) is easily filled into a porous substrate.

[0067] In Ar 1The number of ion exchange groups per aromatic ring constituting the main chain may be one or more, and is preferably 1 to 2 from the viewpoint of ion conductivity and polymer stability.

[0068] As the composition of Ar 1 The aromatic ring of the main chain may be a condensed ring such as a naphthalene ring or an anthracene ring, in addition to a benzene ring, or a heterocyclic ring containing an oxygen atom (O), a nitrogen atom (N), or a sulfur atom (S) (e.g., thiophene, etc.). In addition, these aromatic rings may also be structures connected by single bonds. As structures connecting multiple rings by single bonds, for example, biphenyl, terphenyl, fluorene, etc. may be cited.

[0069] CompositionAr 1 The aromatic ring in the main chain may have a substituent other than the ion exchange group in addition to the above-mentioned ion exchange group. Examples of the substituent include an alkyl group having 1 to 20 carbon atoms which may have a substituent, a phenyl group which may have a substituent, and a halogenated group.

[0070] Specific examples of the alkyl group include methyl, ethyl, propyl, n-butyl, tert-butyl, pentyl, hexyl, octyl and other alkyl groups, and as a substituent, it may also have a phenyl group, a halide group, etc. In addition, as a substituent that the phenyl group may have, an alkyl group having 1 to 6 carbon atoms, a halide group, etc. In addition, as the halide group, a fluoro group, a chloro group, a bromo group, an iodo group, etc. may be mentioned.

[0071] In view of excellent mechanical strength, chemical durability, and ion conductivity, the Ar of the polymer (A) is preferably 1 Among them, a group represented by any one of the following formulae (a-1) to (a-10) is preferred.

[0072] It should be noted that the multiple Ar 1 They can be the same as each other or different.

[0073]

Chemical formula 4

[0074]

[0075] Among them, R a Each independently represents a hydrogen atom, an ion exchange group or a substituent having no ion exchange group, and multiple R a can be the same or different from each other, R a At least one R a For ion exchange groups.

[0076] It should be noted that the wavy line indicates the 2 The bond of the combination.

[0077] CompositionAr2 The main chain aromatic rings may be the same as the above Ar 1 The same substance and the groups connected through the spiro atoms. 2 The aromatic ring in the may also have other substituents other than the anion exchange group. As other substituents, there can be mentioned 1 The substituents other than the ion exchange groups in the present invention are the same substituents.

[0078] As Ar 2 In the group in which two or more aromatic rings are connected by a spiro atom, for example, a group represented by the following formula (c1) can be cited. In addition, as a group in which two or more aromatic rings are connected by a single bond, for example, a group represented by the following formula (c2) to (c4) can be cited. It should be noted that the wavy line represents the 1 From the perspective of the filling property of the polymer into the porous substrate, Ar 2 Preferably there are no spiro atoms.

[0079]

Chemical formula 5

[0080]

[0081] Among them, R c Each is independently a hydrogen atom, a halide group or an organic group.

[0082] From the perspective of chemical durability and ease of filling into pores, the weight average molecular weight of polymer (A) can be appropriately adjusted, for example, it can be set to a range of 10,000 to 1,000,000. From the perspective of chemical durability, it is preferably 30,000 or more, and more preferably 100,000 or more. In particular, when the porous substrate is a polyolefin-based porous substrate, even if the weight average molecular weight of polymer (A) is 100,000 or more, it is easy to be filled into the pores. It should be noted that the weight average molecular weight is a polystyrene-converted value measured by GPC (gel permeation chromatography).

[0083] It should be noted that the polymer (A) may be composed only of the structural unit represented by the general formula (1) (also referred to as structural unit (1)), or may have other structural units. Examples of other structural units include Ar in the structural unit (1). 1 In addition, other structures that may be produced in the synthesis may also be included.

[0084] Among polymers (A), the following polymers (A1) to (A4) are preferred. It should be noted that, from the perspective of the filling property of the polymer into the porous substrate, polymer (A2), polymer (A3) or polymer (A4) are preferred, and polymer (A2) or polymer (A3) is preferred. In addition, from the perspective of the filling property, mechanical strength and chemical durability of the polymer, polymer (A3) is preferred. These polymers are described in detail below.

[0085] Polymer (A1)

[0086] The polymer (A1) has a repeating unit represented by the following general formula (1-1).

[0087]

Chemical formula 6

[0088]

[0089] Among them, R 1 ~R 10 are each independently a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or a phenyl group, Ar 1 The same as the substance in the above formula (1), and the preferred aspects are also the same.

[0090] As R 1 ~R 10 The alkyl group having 1 to 4 carbon atoms in the polymer (A1) may be a methyl group, an ethyl group, a propyl group, a tert-butyl group or the like. 1 and R 10 At least one of them is preferably an alkyl group, and R 1 and R 10 More preferably, it is an alkyl group. 1 and R 10 More preferably, it is tert-butyl. 1 and R 10 At least one of the R has a bulky substituent, which inhibits the aggregation of the polymer caused by π-π stacking and improves the solubility in the solvent. 1 ~R 8 Each independently is preferably a hydrogen atom or a methyl group, more preferably a hydrogen atom.

[0091] The polymer (A1) has Ar 1 The structure of alternating with the spirobifluorene skeleton, Ar 1It has an anion exchange group. Each element constituting the main chain skeleton of the polymer (A1) belongs to an aromatic ring, or a spiro atom without a hydrogen atom. Since the main chain skeleton does not have an ether bond, decomposition in the presence of an alkali or a free radical is suppressed, and the chemical durability is excellent. In addition, the spirobifluorene skeleton has a structure in which two fluorenes are twisted at right angles by spiro atoms. By making the fluorene skeleton constitute the main chain, the main chain as a whole becomes a state with multiple bends. Therefore, the planarity of the main chain is reduced, π-π stacking is hindered, the solubility in the solvent is also excellent, and the operability when filling the porous substrate is excellent.

[0092] The method for synthesizing the polymer (A1) is not particularly limited, and a preferred example thereof includes the method of the following Scheme A1.

[0093]

Chemical formula 7

[0094] Option A1

[0095]

[0096] In Scheme A1, R a represents anion exchange group, R b In the general formula (1-1), 1 and R 10 Equivalent substituents.

[0097] In the above example of Scheme A1, the b Compound (B) is used to synthesize compound (C) having a brominated spirobifluorene skeleton (steps (i) to (vii)). In addition, bis(pinacolato)diboron (bis(pinacolato)diboran) is reacted with a bromide (D) having a desired aromatic ring (a benzene ring in the example of Scheme A1) to synthesize Ar in the general formula (1-1): 1 The compound (E) which is a precursor of the compound (C) is prepared (step (viii)). After polymerizing the compound (C) and the compound (E), the desired anion exchange group is introduced to obtain a polymer represented by the general formula (1-1) (steps (ix) to (xi)). It should be noted that the reaction conditions of the above steps can be determined by referring to known reactions.

[0098] Polymer (A2)

[0099] The polymer (A2) has a repeating unit represented by the following general formula (1-2).

[0100]

Chemical formula 8

[0101]

[0102] Among them, R ais a group having an anion exchange group, Ar 2 The same as those in the general formula (1).

[0103] The polymer (A2) is a polymer having two or more of the structural units (1-2) and is a compound having a wholly aromatic main chain. Since the polymer (A2) has such a structure, it has excellent durability against alkalis, free radicals, and the like.

[0104] Among them, Ar in polymer (A2) 2 Preferred are phenylene, biphenylene, and triphenylene, and more preferred are p-phenylene (the following formula (Ar-1)), 4,4'-biphenylene (the following formula (Ar-2)), or 4,4'-triphenylene (the following formula (Ar-3)).

[0105]

Chemical formula 9

[0106]

[0107] Where R is Ar 2 The substituent that may be present is r, which is an integer of 0 to 4, and a plurality of Rs and r may be the same or different.

[0108] In Ar 2 When it is p-phenylene, 4,4'-biphenylene or 4,4'-triphenylene, the main chain skeleton of the polymer (A2) is easily arranged in a zigzag shape as shown in the following formula. 2 In the case of p-phenylene, the same is true for 4,4'-biphenylene or 4,4'-triphenylene. As shown in the following formula, the main chain skeleton of the polymer (A2) is easily arranged in a zigzag shape, and each R a It is easy to arrange it outside the folded back of the backbone. Therefore, the aggregation in the molecule caused by the folding back of the main chain is suppressed. As a result, it becomes a polymer that can form an electrolyte membrane with excellent ion conductivity.

[0109]

Chemical formula 10

[0110]

[0111] Among them, the group R having an anion exchange group in the polymer (A2) a The following formula (R a -1) shown in the group.

[0112]

Chemical formula 11

[0113]

[0114] Among them, R b2is an anion exchange group, and p2 is an integer of 1 to 20. In addition, the wavy line represents a bond to the benzene ring.

[0115] In the above formula (R a -1), the carbon atom adjacent to the benzene ring constituting the main chain is a quaternary carbon. Therefore, π-π stacking between polymers (A2) is suppressed. As a result, the aggregation of polymer (A2) is suppressed, it is easily soluble in a solvent, and the operability in the process of film formation is excellent.

[0116] P2 represents {(from R b2 The carbon number of the quaternary carbon)-1} may be appropriately adjusted within the range of 1 to 20. Among them, 1 to 15 are preferred, 1 to 12 are more preferred, and 1 to 6 are further preferred.

[0117] The method for synthesizing the polymer (A2) is not particularly limited, and a preferred example thereof is the method of the following Scheme A2.

[0118]

Chemical formula 12

[0119] Option A2

[0120]

[0121] Among them, X, X 1 Represents a halogen atom, Ar 2 and p2 as above. As X 1 A halogen atom is preferably Br.

[0122] In the example of the above scheme A2, first, compound (H) and a compound having a desired Ar 2 Compound (I) is prepared by polymerizing compound (H) and compound (I) to obtain a polymer having a structural unit shown in (J). Next, a desired anion exchange group is introduced into polymer (J) to obtain polymer (A2). In the above scheme A2, although quaternary ammonium is introduced, other ionic functional groups can also be introduced based on this. It should be noted that the reaction conditions of the above steps can be determined by referring to known reactions.

[0123] Polymer (A3)

[0124] In the repeating unit represented by the general formula (1), Ar 2 The two ends have a partial structure represented by the following formula (2). 2 is a divalent group containing an aromatic ring having a fluorine group (-F) at the α position of the terminal carbon atom. 2 The end of Ar 1It should be noted that the wavy line represents the carbon atom bound to Ar 1 The dotted line indicates that part of the aromatic ring is omitted.

[0125]

Chemical formula 13

[0126]

[0127] The polymer (A3) has Ar 1 with Ar 2 Alternating configuration structure, Ar 1 With anion exchange group, Ar 2 It has a partial structure (2) containing a fluorine group (-F). Ar constituting the main chain 1 and Ar 2 Each of the two groups has an aromatic group and has excellent chemical durability against alkali and free radicals. In addition, in the polymer (A3), the Ar having an ion exchange group connected to the end of the side chain via an alkyl chain is 1 With Ar without ion exchange groups 2 Alternate configuration. Due to such a structure, solubility and ion conductivity are excellent. In addition, the compound having partial structure (2) has high reactivity with the compound shown in formula (4) described later, and a polymer with higher molecular weight can be manufactured. By using this polymer with high molecular weight, a film with more excellent durability can also be formed.

[0128] For example, Ar 2 As in the formula (b-1) described later, two partial structures (2) may be present in one ring structure (e.g., a benzene ring), or one CF bond may constitute two partial structures (2) as in the formula (b-2) described later. In addition, in the case of the above-mentioned chain polycyclic hydrocarbon, each of the two ring structures possessed by the chain polycyclic hydrocarbon has one partial structure (2), and these rings may be directly connected or connected via the above-mentioned connecting group, or one of the multiple ring structures may have two partial structures (2). Ar in the polymer (A3) 2 Preferably there is no spiro atom.

[0129] In the polymer (A3), the Ar 2 Preferably, it is one or more selected from the following formula (d1) to the following formula (d9). 1 The combination key.

[0130]

Chemical formula 14

[0131]

[0132] Among them, R d Each is independently a hydrogen atom, a halide group or an organic group.

[0133] As the above R d The halogeno group in the halogenated group includes a fluoro group, a chloro group, a bromo group and an iodo group, among which a fluoro group is preferred.

[0134] In addition, as the above R d The organic group in the formula (a) includes, for example, a linear or branched alkyl group having 1 to 20 carbon atoms (excluding the carbon number of the substituent) which may have a substituent (for example, a halogeno group).

[0135] From the perspective of ease of manufacture, the above Ar 2 Preferably, the following formulas (d10) to (d14) are used. 1 The combination key.

[0136]

Chemical formula 15

[0137]

[0138] The method for synthesizing the polymer (A3) is not particularly limited, and a preferred example thereof is the method of the following Scheme A3.

[0139]

Chemistry 16

[0140] Option A3

[0141]

[0142] Among them, X 1 Each independently is Br or I, Ar 3 is an aromatic group having a functional group selected from a halide group, a sulfonate group, a phosphate group, a carboxylate group, an imidazole group and an amino group, Ar 2 The same as in polymer (A3).

[0143] Since X of compound (4) 1 With the Ar of compound (5) 2 The hydrogen atoms of the partial structure (5a) shown below have excellent reactivity, and thus a high molecular weight (for example, a weight average molecular weight of 30,000 or more, preferably 100,000 or more) ion conductive polymer can be synthesized relatively easily.

[0144]

Chemical formula 17

[0145]

[0146] In the above scheme A3, first, prepare a 3The compound (4) and the compound having the desired Ar 2 Then, by reacting these compounds, for example, in a solvent in the presence of a Pd complex, a ligand, a carboxylic acid (RCO2H) and a base at 80 to 140°C for 1 to 48 hours, a polymer having the structural unit (3) is obtained.

[0147] Next, the desired ion exchange group is introduced into the polymer having the structural unit (3) to obtain the polymer (A3). Thus, the polymer (A3) can be easily produced with very few synthesis steps by using the compound (4) and the compound (5) as raw materials.

[0148] Polymer (A4)

[0149] The polymer (A4) has a repeating unit represented by the following general formula (1-4).

[0150]

Chemistry 18

[0151]

[0152] Among them, cyclic Ar 11 and cyclic Ar 12 It is a ring condensed with a benzene ring, and as a whole it is a condensed ring of three or more rings with aromatic properties. 1 The same as those in the general formula (1).

[0153] The polymer (A4) has Ar 1 Ar consisting of three or more condensed rings 2 Alternating repeating structure, Ar 1 Generally, polymers containing a large number of ion exchange groups tend to swell easily, but the polymer (A4) has an anion exchange group. 1 with Ar 2 The alternating repetition and π-π stacking of three or more fused rings provide excellent anti-swelling properties.

[0154] Cyclic Ar 11 and cyclic Ar 12 is an aromatic ring which may have a hetero atom. Examples of the hetero atom include N (nitrogen atom), O (oxygen atom), and S (sulfur atom). 11 and cyclic Ar 12 In view of the swelling resistance, condensed rings of three or more rings are preferred. On the other hand, condensed rings of five or less rings are preferred, and condensed rings of four or less rings are more preferred, in view of improving the ion exchange capacity of the polymer (A4).

[0155] As preferred specific examples of the condensed ring, the following examples can be cited. It should be noted that the wavy line represents the same as Ar 1In addition, the hydrogen atom may be substituted by a group having no anion exchange group.

[0156]

Chemical formula 19

[0157]

[0158] The polymer (A4) is preferably synthesized by preparing a precursor (1-5) having a repeating unit represented by the following general formula (1-5), and removing the substituent (TL) after filling the porous substrate.

[0159]

Chemical formula 20

[0160]

[0161] Wherein, LT is a group represented by the general formula (LT1) to (LT3), R 11 are each independently an alkyl group having 1 to 6 carbon atoms, R 12 is an alkyl group or a phenyl group having 1 to 6 carbon atoms, Ar 1 ,Ar 11 ,Ar 12 The same as the substance in the general formula (1-4). 11 and R 12 The alkyl group having 1 to 6 carbon atoms may be a linear or branched alkyl group, and specific examples thereof include methyl, ethyl, propyl, n-butyl, tert-butyl, pentyl, and hexyl.

[0162] As mentioned above, polymer (A4) has excellent anti-swelling properties. Therefore, there are problems such as difficulty in dissolving in various organic solvents and poor operability during processing. The above-mentioned precursor introduces the substituent (TL) shown in the above-mentioned general formula (LT1) to (LT3) at the position corresponding to the condensed ring of polymer (A4), and the substituent (TL) is large in volume and can be relatively easily detached under the action of heat or light. The precursor (1-5) hinders the π-π stacking of the hydrophobic part through the substituent, thereby improving the solubility in various organic solvents. Therefore, the above-mentioned precursor has excellent operability and is easy to fill into a porous substrate. It should be noted that the substituent (TL) can be removed by heating or light irradiation.

[0163] The method for synthesizing the precursor is not particularly limited, and a suitable specific example thereof includes the method of the following Scheme A4.

[0164]

Chemical formula 21

[0165] Plan A4

[0166]

[0167] An example of each step of the above scheme A4 is described.

[0168] Step (i): Prepare a toluene solution of the above compound (1), add diethyl azodicarboxylate (DEAD) and heat under reflux to obtain the above compound (2).

[0169] Step (ii): In addition, a solution of the above compound (3) in N,N-dimethylformamide (DMF) is prepared, and the above compound (4) is obtained by adding bis(pinacol)diboron, potassium acetate (KOAc), [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride (Pd(dppf)Cl2) and heating to 90°C.

[0170] Step (iii): In the toluene solution of the above-mentioned compound (2) and the above-mentioned compound (4), tripotassium phosphate (K3PO4) and tetrakis(triphenylphosphine)palladium (Pd(PPH3)4) are added and heated to 100°C for polymerization to obtain the above-mentioned compound (5).

[0171] Step (iv): Add the obtained compound (5), N-bromosuccinimide (NBS) and azobisisobutyronitrile (AIBN) into chlorobenzene, mix them, and heat to 110° C. to obtain the above compound (6).

[0172] Step (v): The obtained compound (6) is heated to 50° C. in a DMF / THF (tetrahydrofuran) mixed solvent to obtain the precursor represented by the above chemical formula (7).

[0173] <Method for producing pore-filled film>

[0174] As an example of a method for producing a pore-filled membrane, there can be mentioned a method of providing a polyarylene polymer on a porous substrate and drying the resulting polymer.

[0175] As a method for imparting a polyarylene polymer to a porous substrate, for example, a solution of the polyarylene polymer is prepared, and a method such as an immersion method, a spray method, a spin coating method, a barcode method, etc. can be cited. After the polyarylene polymer solution is infiltrated into the porous substrate, a pore-filled membrane can be obtained by drying. It should be noted that the filling of the polyarylene polymer in the porous substrate can be confirmed, for example, by Raman analysis.

[0176] Since the present pore-filled membrane is excellent in chemical durability, mechanical strength and ion conductivity, it can be suitably used as an electrolyte membrane for fuel cells, electrolysis devices and the like.

[0177]

Electrolysis device

[0178] The electrolysis device disclosed in the present invention is characterized by comprising the present pore-filled membrane. The electrolysis device can, for example, adopt the following structure: in an electrolytic cell, the present pore-filled membrane is used as an electrolyte membrane, an anode and a cathode are stacked on a membrane electrode assembly structure of the electrolyte membrane, and an object can be electrolyzed (oxidation-reduction reaction) by the membrane electrode assembly to obtain a target object.

[0179] When the electrolyte membrane is applied to water electrolysis, a proton conductive or anion conductive electrolyte membrane is used as the electrolyte membrane. For example, an anode is arranged on one surface of a proton conductive electrolyte membrane, and a cathode is arranged on the other surface, so that protons generated at the anode move to the cathode through the electrolyte membrane and combine with electrons at the cathode to obtain hydrogen. When a proton conductive membrane is used, the chemical reaction equations of each pole are as follows.

[0180] Anode: 2H2O→O2+4H + +4e -

[0181] Cathode: 2H + +2e - →H2

[0182] In addition, as another electrolysis technology, there is an electrolysis technology for electrolyzing carbon dioxide to produce formic acid. For example, protons generated at the anode are moved to the cathode through the electrolyte membrane and react with carbon dioxide supplied to the cathode to produce formic acid. The chemical reaction equations of each pole are shown below.

[0183] Anode: 2H2O→O 2 +4H + +4e -

[0184] Cathode: CO2+2H + +2e - →HCOOH

[0185] Reference Figure 2 , the structure of the water electrolysis device is explained. Figure 2 This is a schematic cross-sectional view showing an example of the main parts of a water electrolysis device. Figure 2The water electrolysis device 1 shown in the example includes an electrolyte membrane 5 using the present pore-filled membrane, an anode 10 arranged on one surface of the electrolyte membrane 5, a cathode 20 arranged on the other surface, a power source 7 connected to the anode 10 and the cathode 20, and a water supply unit that supplies water or an alkaline aqueous solution to the cathode 20. The anode 10 only needs to have at least an anode catalyst 11, and may also have a first diffusion layer 12. In addition, the cathode 20 only needs to have at least a cathode catalyst 21, and may also have a second diffusion layer 22. The membrane electrode assembly 8 includes at least an anode catalyst 11 arranged on one surface of the membrane 5 and a cathode catalyst 21 arranged on the other surface. In Figure 2 In the example, a cell 6 is further configured with separators 13 and 23 on the outside of the anode 10 and the cathode 20, respectively. The water electrolysis device 1 may be a single cell 6 or a device in which a plurality of cells 6 are stacked. In addition, the water supply unit may supply water to at least one of the cathode and the anode.

[0186] By using the pore-filled membrane as the electrolyte membrane 5 , a water electrolysis device having high water electrolysis performance and excellent durability can be obtained.

[0187] When the water electrolysis device is a solid alkaline water electrolysis device, for example, when water or an alkaline aqueous solution is supplied to the cathode 20 side and a voltage is applied to both electrodes, the following reaction occurs on the cathode 20 side to generate hydrogen.

[0188] 2H2O+2e - →2OH - +H2

[0189] Hydroxide ion (OH - ) permeates the electrolyte membrane 5 and moves to the anode 10. The following reaction occurs at the anode 10 to generate oxygen.

[0190] 2OH - →H2O+1 / 2O2+2e -

[0191] The generated hydrogen and oxygen are discharged from the pool 6 through the gas flow paths 14 and 24 provided in the partitions 13 and 23, respectively. The gas flow path is connected to a storage tank or the like through a gas-liquid separator (not shown), for example, and the hydrogen and oxygen are stored in a storage tank or the like after water is separated from the gas-liquid separator.

[0192] In the present water electrolysis device, the water supplied may be pure water or an alkaline aqueous solution. By using an alkaline aqueous solution, water electrolysis can be performed more efficiently than with pure water. Since the pore-filled membrane is used as the anion conductive membrane 5, durability is excellent even when an alkaline aqueous solution is used. The solute in the alkaline aqueous solution is not particularly limited, and for example, it can be set to 1M potassium hydroxide or the like.

[0193] The anode 10 has at least an anode catalyst 11 and may also have a first diffusion layer 12. The anode catalyst 11 is preferably a metal or a metal alloy. The metal or metal alloy can be appropriately selected from known metals or metal alloys, for example, platinum, cobalt, nickel, palladium, iron, silver, gold, copper, iridium, molybdenum, rhodium, chromium, tungsten, manganese, ruthenium, metal compounds of these metals, metal oxides, and alloys containing two or more of these metals.

[0194] In addition, from the perspective of the contact area with water and the diffusion of water or gas, the anode catalyst 11 is preferably a porous body. Examples of porous catalysts include metal particle connections formed by fusing the above metal particles, and porous bodies such as felt (non-woven fabric), mesh, etc. formed by foams (foams), wires, or fibers of the above metals.

[0195] The anode catalyst 11 may also be used by coating a known electrolyte polymer (ionomer) on the surface of the above-mentioned metal. On the other hand, in the present embodiment, the alkaline aqueous solution moves in the membrane electrode assembly 8 and exhibits ion conductivity, so the ion conductivity is excellent even without using an electrolyte polymer. In addition, by not coating the electrolyte polymer on the anode catalyst, the catalytic activity is further improved.

[0196] Among them, the anode catalyst preferably has nickel foam. In addition, considering both durability and high activity, the following catalysts are preferred: (I) a catalyst having a nickel oxide layer containing NiOOH and a NiFe layer in sequence on nickel foam (hereinafter also referred to as catalyst (I)), or (II) a catalyst having a phosphide layer containing Ni2P and Fe2P on nickel foam (hereinafter also referred to as catalyst (II)).

[0197] <Catalyst (I)>

[0198] Reference Figure 5 , a catalyst having a nickel oxide layer containing NiOOH and a NiFe layer in that order on a nickel foam is described. Figure 5 is a schematic cross-sectional view of the catalyst. Figure 5 The catalyst 30 shown in the example has a nickel oxide layer 32 containing NiOOH and a layer 33 containing NiFe on a nickel foam 31 in this order. Figure 5 In the example of , the inner surface of the pores also has the above-mentioned layer structure. By having the above-mentioned layer structure, when using nickel foam, it has excellent durability even in an alkaline environment and becomes a highly active catalyst.

[0199] The nickel oxide layer 32 is characterized by containing NiOOH. The catalyst has the nickel oxide layer, so that it has better durability and activity than a catalyst having a NiFe-containing layer formed directly on nickel foam.

[0200] The nickel oxide layer only needs to contain NiOOH, and may contain other nickel oxides within the range that the effects of the present invention are achieved. Examples of other nickel oxides include NiO and Ni2O3.

[0201] The ratio of NiOOH in the nickel oxide layer is preferably 50 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more, relative to 100 mass % of the nickel oxide layer.

[0202] In the catalyst (I), the thickness of the nickel oxide layer is preferably 50 to 500 nm, more preferably 100 to 400 nm. If the nickel oxide layer is 50 nm or more, a catalyst with better durability and activity can be obtained. In addition, when the thickness of the nickel oxide layer is 500 nm or less, a sufficient effect can be obtained.

[0203] The catalyst (I) has a NiFe-containing layer on the nickel oxide layer. By forming the NiFe layer on the nickel oxide layer, leaching of Fe is suppressed, and the catalyst has excellent durability.

[0204] The ratio of Fe in the catalyst (I) is preferably 4 to 20% by mass relative to the total amount of the catalyst containing nickel foam. If Fe is 4% by mass, a catalyst with better durability and activity can be obtained. In addition, sufficient effects can be obtained when Fe is below 20% by mass.

[0205] The thickness of the catalyst (I) is preferably 100 to 2000 μm, more preferably 200 to 1600 μm. When the thickness is 100 μm or more, the catalyst has better durability and activity.

[0206] It should be noted that the thickness of each layer can be measured by scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX) mapping. In addition, the composition of each layer can be measured by X-ray photoelectron spectroscopy (XPS).

[0207] (Method for producing catalyst (I))

[0208] Next, the method for producing the catalyst (I) is described. The method for producing the catalyst (I) includes the step of first forming a nickel oxide layer containing NiOOH on nickel foam. By forming the nickel oxide layer containing NiOOH on nickel foam, it is easy to form a NiFe-containing layer, and leaching of the NiFe-containing layer is suppressed.

[0209] As a method for forming a nickel oxide layer on nickel foam, for example, a method of forming by spraying NiOOH particles by aerosol deposition method or the like, or a method of oxidizing the surface of nickel foam, etc. From the aspect of easily forming a nickel oxide layer on the inner surface of nickel foam, a method of oxidizing the surface of the substrate is preferred. As a method for oxidizing the surface of the substrate, electrochemical oxidation is preferred.

[0210] Electrochemical oxidation can include, for example, a method in which a nickel foam of a desired shape is first prepared, the nickel foam is immersed in an alkaline electrolyte, and a voltage is applied to oxidize the nickel foam. It should be noted that the nickel foam can be manufactured by a known method, or commercially available products can be used. In addition, in the case where the nickel foam has an oxide layer, an acid treatment can be performed as required. The thickness of the nickel oxide layer can be adjusted by adjusting the application time of the voltage.

[0211] In addition, the formation of the nickel oxide layer can be confirmed by Raman spectroscopy or the like.

[0212] Next, a NiFe-containing layer is formed on the nickel oxide layer.

[0213] As a method for forming a NiFe-containing layer on the nickel oxide layer, for example, there can be mentioned a method of spraying NiFe particles by aerosol deposition or the like, or a method of electrodepositing Fe, etc. From the perspective of easily forming a NiFe-containing layer on the inner surface of the nickel foam, the method of electrodepositing Fe is preferred.

[0214] Electrodeposition of Fe can be exemplified by the following examples: 2+ The intermediate product is immersed in an electrolyte solution and a voltage is applied to perform electrodeposition. By adjusting the voltage application time, the thickness of the NiFe-containing layer and the Fe ratio in the catalyst can be adjusted.

[0215] <Catalyst (II)>

[0216] Reference Figure 6 , a catalyst having a phosphide layer containing Ni2P and Fe2P on nickel foam is described. Figure 6 is a schematic cross-sectional view of the catalyst. Figure 6 The catalyst 40 shown in the example has a phosphide layer 42 containing Ni2P and Fe2P on a nickel foam 41. Figure 6 In the example of , the inner surface of the pores also has the above-mentioned layer structure. By having the above-mentioned layer structure, when using nickel foam, it has excellent durability even in an alkaline environment and becomes a highly active catalyst.

[0217] The shape of the nickel foam 41 is the same as that of the catalyst (I), and the preferred method is also the same.

[0218] In the catalyst (II), the phosphide layer 42 contains Ni2P and Fe2P. The phosphide layer of the catalyst (II) contains Fe2P in particular, so that the durability and activity are more excellent than those of a catalyst having a layer containing only Ni2P formed on nickel foam.

[0219] The thickness of the catalyst (II) is preferably 100 to 2000 μm, more preferably 200 to 1600 μm. When the thickness is 100 μm or more, the catalyst has better durability and activity.

[0220] From the viewpoint of durability and activity, the proportion of P in the catalyst (II) is preferably 10 to 50% by mass, more preferably 20 to 30% by mass, based on the total amount of the catalyst.

[0221] From the viewpoint of durability and activity, the proportion of Fe in the catalyst (II) is preferably 1 to 10% by mass, more preferably 1 to 3% by mass, based on the total amount of the catalyst.

[0222] From the aspects of durability and activity, the total ratio of Ni2P and Fe2P in the phosphide layer is preferably 50 to 100 mass %, more preferably 70 to 100 mass %, and further preferably 85 to 100 mass % relative to the total amount of the phosphide layer.

[0223] In addition, from the perspective of durability and activity, the ratio of Ni2P to Fe2P in the phosphide layer is preferably 9:1 to 5:5 in terms of mass ratio.

[0224] In the catalyst (II), the thickness of the phosphating layer is preferably 50 to 500 nm, more preferably 100 to 400 nm. If the phosphating layer is 50 nm or more, a catalyst having better durability and activity can be obtained. In addition, when the thickness of the phosphating layer is 500 nm or less, a sufficient effect can be obtained.

[0225] It should be noted that the thickness of the phosphated layer can be measured by scanning electron microscopy (SEM) and energy dispersive X-ray analysis (EDX) and the composition of the phosphated layer can be measured by X-ray photoelectron spectroscopy (XPS).

[0226] (Method for producing catalyst (II))

[0227] Next, the method for producing the catalyst (II) is described. As the method for producing the catalyst (II), for example, a method of immersing nickel foam in an iron ion solution and phosphating the nickel foam after immersion can be cited. According to this production method, a phosphating layer containing Ni2P and Fe2P can be easily formed on the nickel foam, and the obtained catalyst has excellent durability and activity.

[0228] In this manufacturing method, first, nickel foam of a desired shape is prepared, and the nickel foam is immersed in an iron ion solution. The iron ion solution is prepared by dissolving a dissociable iron compound in a solvent. As the iron compound, for example, ferric chloride and the like can be cited, preferably an iron compound that produces trivalent iron ions. The solvent generally includes water, and may also include other solvents. As other solvents, solvents having an affinity with water are preferred, and methanol, ethanol and the like can be cited. The concentration of iron ions in the solution is not particularly limited, and for example, can be set to 0.01 to 0.5 mol / l, etc.

[0229] The immersion time of the nickel foam is not particularly limited, and can be appropriately adjusted within a range of, for example, 10 minutes to 6 hours. The nickel foam after immersion may be dried as necessary.

[0230] Next, the nickel foam after impregnation is phosphated. By phosphating the nickel foam while the iron ions are attached to the surface of the substrate, a phosphated layer containing Ni2P and Fe2P can be easily formed.

[0231] The phosphating method is not particularly limited, but preferably a method of heating the nickel foam in the presence of a phosphorus compound is used. Specifically, for example, a method of placing the phosphorus compound and the impregnated nickel foam in a furnace and heating them in an inert gas atmosphere such as nitrogen is used.

[0232] In the heating process, when an inert gas is supplied into the furnace, by arranging a phosphorus compound on the upstream side and arranging nickel foam on the downstream side, phosphating can be performed efficiently.

[0233] The phosphorus compound is preferably a compound that decomposes by heating. Specific examples of the phosphorus compound include sodium hypophosphite and the like.

[0234] The heating temperature can be appropriately adjusted in consideration of the decomposition temperature of the phosphorus compound and the like, and can be, for example, in the range of 300 to 600°C, preferably in the range of 350 to 550°C.

[0235] The anode 10 may further include a first diffusion layer 12 in addition to the anode catalyst 11. The first diffusion layer 12 may be appropriately selected from known gas diffusion layers, and examples thereof include foamed metal layers such as nickel foam and porous carbon layers.

[0236] The cathode 20 has at least a cathode catalyst 21 and may also have a second diffusion layer 22. The cathode catalyst 21 is preferably a metal or a metal alloy. The metal or metal alloy can be appropriately selected from known metals or metal alloys, for example, platinum, cobalt, nickel, palladium, iron, silver, gold, copper, iridium, molybdenum, rhodium, chromium, tungsten, manganese, ruthenium, metal compounds of these metals, metal oxides, and alloys containing two or more of these metals.

[0237] In addition, from the perspective of the contact area with water and the diffusion of water or gas, the cathode catalyst 21 is preferably a porous body. Examples of porous catalysts include metal particle connections formed by fusing the above metal particles to form a catalyst, or porous bodies such as felt (non-woven fabric), mesh, etc. formed by foamed bodies (foam), linear, or fibrous metals of the above metals.

[0238] The cathode catalyst 21 may also be used by coating the above metal surface with a known electrolyte polymer. On the other hand, in this embodiment, the alkaline aqueous solution moves in the membrane electrode assembly 8 and exhibits ion conductivity, so even if an electrolyte polymer is not used, the ion conductivity is excellent. In addition, by not coating the cathode catalyst with an electrolyte polymer, the catalytic activity is further improved.

[0239] Among them, the cathode catalyst preferably has a porous body of metal or metal alloy. In addition, from the perspective of balancing durability and high activity, it is preferably a catalyst having a layer containing Ru and a metal phosphide from the metal or metal alloy on the porous body of the metal or metal alloy (hereinafter also referred to as catalyst (III)).

[0240] <Catalyst (III)>

[0241] Reference Figure 4 , a catalyst having a layer containing Ru and a phosphide on a porous body of a metal or a metal alloy is described. Figure 4 is a schematic cross-sectional view of the catalyst. Figure 4 The catalyst 50 shown in the example of FIG. 1 has a layer 52 containing Ru and a metal phosphide on a porous body 51. By having such a layer structure, both durability and high activity are achieved.

[0242] The catalyst (III) is characterized in that it has a layer containing Ru and a metal phosphide on a porous body. The composite layer of Ru and the metal phosphide has better durability and activity than a layer containing no phosphide.

[0243] The thickness of the catalyst (III) is preferably 100 to 2000 μm, more preferably 200 to 1600 μm. When the thickness is 100 μm or more, the catalyst has better durability and activity.

[0244] The metal (M) constituting the porous body can be any metal, but from the aspects of the ease of manufacture of the catalyst, it is preferred that the metal can form a phosphide. As a specific example of such a metal, Fe, Cu, Ni, Ti, etc. can be cited. From the aspects of the durability and activity of the catalyst, Ni or Ti is preferred. The metal constituting the porous body can be a monomer or an alloy containing two or more. In addition, within the scope of the effect of the present invention, the metal substrate can also contain other elements.

[0245] From the viewpoint of durability and activity, the ratio of Ru in the catalyst (III) is preferably 0.1 to 40% by mass, more preferably 0.5 to 30% by mass, based on the total amount of the catalyst.

[0246] From the viewpoint of durability and activity, the proportion of P in the catalyst (III) is preferably 10 to 50% by mass, more preferably 20 to 30% by mass, based on the total amount of the catalyst.

[0247] In addition, from the viewpoint of durability and activity, in the layer containing Ru and the metal phosphide, the ratio of Ru to the metal phosphide is preferably 9:1 to 5:5 in terms of mass ratio.

[0248] In the catalyst (III), the thickness of the layer containing Ru and the metal phosphide is preferably 50 to 500 nm, more preferably 100 to 400 nm. If the layer containing Ru and the metal phosphide is 50 nm or more, a catalyst having better durability and activity can be obtained. In addition, when the thickness of the layer containing Ru and the metal phosphide is 500 nm or less, a sufficient effect can be obtained.

[0249] It should be noted that the thickness of the above-mentioned layer can be measured by mapping using a scanning electron microscope (SEM) or an energy dispersive X-ray analyzer (EDX, EDS). In addition, the composition of the above-mentioned layer can be measured by X-ray photoelectron spectroscopy (XPS).

[0250] (Method for producing catalyst (III))

[0251] Next, the method for producing the catalyst (III) is described. As a method for producing the catalyst (III), for example, a method of immersing a porous body of a metal or metal alloy in a Ru ion solution and phosphating the porous body after the immersion can be cited. According to this production method, a layer containing Ru and a metal phosphide can be easily formed on a metal substrate layer, and the obtained catalyst has excellent durability and activity.

[0252] In this manufacturing method, first prepare the desired porous body and immerse the porous body in a Ru ion solution. The Ru ion solution is prepared by dissolving a dissociable ruthenium compound in a solvent. As the ruthenium compound, for example, ruthenium chloride can be cited. The solvent usually includes water and can also include other solvents. As other solvents, solvents with affinity to water are preferred, and methanol, ethanol, etc. can be cited. The concentration of iron ions in the solution is not particularly limited, for example, it can be set to 0.01 to 0.5 mol / l, etc.

[0253] The impregnation time of the porous body is not particularly limited, and can be appropriately adjusted within the range of 1 to 48 hours, preferably 12 to 36 hours. By impregnating for a long time, it is speculated that electrochemical replacement of the surface metal ions and Ru ions of the porous body will occur, and as a result, the durability of the obtained catalyst is further improved. The porous body after impregnation can be dried as needed.

[0254] Next, the porous body after the impregnation is phosphated (step (II)). By phosphating the porous body in a state where Ru ions are present on the surface of the substrate, a layer containing Ru and a metal phosphide can be easily formed.

[0255] The phosphating method is not particularly limited, but preferably a method of heating the metal substrate in the presence of a phosphorus compound is used. Specifically, for example, a method of placing the phosphorus compound and the impregnated porous body in a furnace and heating them in an inert gas atmosphere such as nitrogen is used.

[0256] In the case where an inert gas is supplied into the furnace during the heating process, phosphating can be efficiently performed by arranging a phosphorus compound on the upstream side and arranging a porous body on the downstream side.

[0257] The phosphorus compound is preferably a compound that decomposes by heating. Specific examples of the phosphorus compound include sodium hypophosphite and the like.

[0258] The heating temperature can be appropriately adjusted in consideration of the decomposition temperature of the phosphorus compound and the like, and can be, for example, in the range of 300 to 600°C, preferably in the range of 350 to 550°C.

[0259] The cathode 20 may further include a second diffusion layer 22 in addition to the cathode catalyst 21. The second diffusion layer 22 may be appropriately selected from known gas diffusion layers, and examples thereof include a foamed metal layer such as nickel foam or a porous carbon layer.

[0260] The present water electrolysis device may also have separators 13 and 23 on the outside of the anode 10 and the cathode 20, respectively. The material of the separator does not need to be a platinum coating, etc., and can be appropriately selected and used as carbon, stainless steel, etc. When the separators 13 and 23 are conductive, the separator 13 may be used as the first main electrode, the separator 23 may be used as the second main electrode, the power supply 7 may be connected to the first main electrode and the second main electrode, and a voltage may be applied to the anode and the cathode.

[0261] The separators 13 and 23 may have gas flow paths 14 and 24. The oxygen gas generated by the anode 10 and the hydrogen gas generated by the cathode 20 are discharged through the gas flow paths 14 and 24, respectively, and stored in storage tanks or the like.

[0262] The power source 7 is not particularly limited and can be appropriately selected from known DC power sources. Since the water electrolysis device has excellent response to input power, it can be suitably used even for renewable energy sources such as solar power generation and wind power generation that vary greatly.

[0263] Fuel Cell

[0264] The fuel cell disclosed in the present invention is characterized by comprising the present pore-filling membrane. The present pore-filling membrane can be applied to both solid alkaline fuel cells and solid polymer fuel cells.

[0265] When the electrolyte membrane is applied to a solid alkaline fuel cell, an anion conductive electrolyte membrane is used as the electrolyte membrane. The structure of the solid alkaline fuel cell can be a conventionally known structure.

[0266] For example, a cathode is arranged on one surface of an electrolyte membrane, and an anode is arranged on the other surface to form a membrane electrode complex. Oxygen is supplied to the cathode, and fuel is supplied to the anode. OH generated at the cathode is - The electrolyte moves to the anode through the electrolyte membrane, where it produces water, thereby generating electricity.

[0267] The fuel can be appropriately selected from conventionally known fuels, and examples thereof include hydrogen, methanol, ethanol, ethylene glycol, formate, hydrazine, sodium borohydride, ammonia, etc., but are not limited thereto.

[0268] As a representative example, reactions at each electrode when hydrogen, methanol, and formate are used as fuels are shown.

[0269] Fuel cells using hydrogen

[0270] Anode: 2OH - +H2→2H2O

[0271] Cathode: O2+2H2O+4e - →4OH -

[0272] Fuel cells using methanol

[0273] Anode: 6OH - +CH3OH→CO2+5H2O

[0274] Cathode: O2+2H2O+4e - →4OH -

[0275] Fuel cells using formate

[0276] Anode: HCOO - +3OH - →2H2O+CO3 2- +2e -

[0277] Cathode: O2+2H2O+4e - →4OH -

[0278] When the electrolyte polymer is applied to a solid polymer fuel cell, a proton conductive electrolyte membrane is used as the electrolyte membrane. The structure of the solid polymer fuel cell can be a conventionally known structure.

[0279] For example, a cathode is arranged on one surface of an electrolyte membrane and an anode is arranged on the other surface to form a membrane electrode assembly, oxygen is supplied to the cathode and fuel is supplied to the anode, and protons generated at the anode move to the anode through the electrolyte membrane, where water is generated, thereby generating electricity.

[0280] The fuel can be appropriately selected from conventionally known fuels, and specifically, the same fuels as those exemplified in the above-mentioned solid alkaline fuel cell can be mentioned.

[0281] As a representative example, the reactions of the electrodes when hydrogen gas is used as fuel are shown.

[0282] Anode: H2→2H + +2e -

[0283] Cathode: O2+4H + +4e - →2H2O

[0284] Figure 5: is a schematic cross-sectional view showing an example of the main parts of a solid polymer fuel cell. The solid polymer fuel cell 60 includes a cell 68 and an external circuit 67, etc. The cell 68 includes a polymer electrolyte membrane 65 as the pore filling membrane, an anode unit 70 for supplying a fuel gas such as hydrogen, and a cathode unit 80 for supplying oxygen. Generally, a battery is constructed by stacking cells 6 according to the required output.

[0285] In the anode unit 70, an anode catalyst layer 71, a diffusion layer 72 and a separator 73 are sequentially arranged from the electrolyte membrane 65 side, and in the cathode unit 80, a cathode catalyst layer 81, a diffusion layer 82 and a separator 83 are sequentially arranged from the electrolyte membrane 5 side. The anode catalyst layer 71 and the diffusion layer 72, and the cathode catalyst layer 81 and the diffusion layer 82 are electrodes, respectively. However, as long as the liquid or gas, the electrolyte and the catalyst layer as the reactant can be in contact at the same time, the diffusion layers 72 and 82 do not necessarily have to be used. In other words, the catalyst layer for the electrode can also be composed of only the anode catalyst layer 71 and / or the cathode catalyst layer 81. In the membrane electrode assembly 68, the electrolyte membrane 65 is at least arranged between the anode catalyst layer 71 and the cathode catalyst layer 81. The external circuit 67 is electrically connected to the anode catalyst layer 71 of the anode unit 70, the cathode catalyst layer 81 of the cathode unit 80, etc.

[0286] In the solid polymer fuel cell 60 constructed as described above, in the anode unit 70, a reducing gas such as hydrogen or a reducing liquid such as methanol and formic acid is supplied to the anode catalyst layer 71 from the gas flow path 74 of the separator 73 through the diffusion layer 72. On the other hand, in the cathode unit 80, an oxidizing gas such as oxygen or air is supplied to the cathode catalyst layer 81 from the gas flow path 84 of the separator 83 through the diffusion layer 82.

[0287] In the case of a cation exchange type using hydrogen as a reducing gas and oxygen as an oxidizing gas, an oxidation reaction of hydrogen occurs in the anode catalyst layer 71 to generate hydrogen ions and electrons. The generated hydrogen ions move to the cathode catalyst layer 81 through the electrolyte membrane 65 having ion conductivity. On the other hand, the generated electrons move to the cathode catalyst layer 81 via the external circuit 7. The hydrogen ions and electrons reaching the cathode unit 80 react with oxygen in the cathode catalyst layer 81 to generate water. That is, in the cathode catalyst layer 81, a reduction reaction of oxygen occurs. The water generated by the reduction reaction is discharged to the outside from the diffusion layer 82 of the cathode unit 80, or is supplied to the polymer electrolyte membrane 65. Electricity is supplied to the outside through this series of reactions. In the case of such a cation exchange type (acid type) fuel cell, as a suitable material for the shell layer, metals with a lower ionization tendency than hydrogen, such as platinum, iridium, ruthenium, palladium, gold or its alloys, etc. can be exemplified. In addition, as a suitable material for the core at this time, platinum, iridium, ruthenium, palladium, cobalt, nickel, iron, silver, gold, copper or its alloys, etc. can be exemplified.

[0288] On the other hand, in the case of an anion exchange type (alkaline) fuel cell, water and oxygen are supplied to the cathode catalyst layer 81 to generate hydroxide ions. The generated hydroxide ions move to the anode catalyst layer 71 through the electrolyte membrane 65 having ion conductivity. Then, the hydroxide ions arriving at the anode catalyst layer side react with the fuel to generate water and electrons. As the fuel, hydrogen, formic acid, alcohol, and ammonia can be listed. The generated electrons move to the cathode catalyst layer 81 via the external circuit 7. Electricity is supplied to the outside through this series of reactions. In the case of such an anion exchange type (alkaline) fuel cell, as a suitable material for the shell layer, a metal selected from platinum, iridium, palladium, ruthenium, nickel, cobalt, iron, gold, silver, and copper or its alloy can be exemplified. In addition, as a suitable material for the core at this time, platinum, iridium, ruthenium, palladium, cobalt, nickel, iron, gold, silver, copper or its alloy can be exemplified.

[0289] Example

[0290] The present invention will be described in more detail below with reference to the following examples. It should be noted that these descriptions do not limit the present invention, and appropriate changes can be made within the scope of the gist.

[0291] [Manufacturing Example 1: Manufacture of anion exchange polymer PFT-C10-TMA]

[0292] (1) Synthesis of Compound I

[0293] A sodium hydroxide (200 g) aqueous solution (600 mL) and n-tetrabutylammonium chloride (556 Mg) were added to a two-necked flask, and stirred under nitrogen. Next, a solution prepared by dissolving 2,7-dibromofluorene (20 mmol) in 1,10-dichlorodecane (200 mmol) while heating was added to the two-necked flask via a syringe.

[0294] Then, after reacting at 90°C under nitrogen for 90 minutes, the obtained reaction solution was cooled to room temperature (25°C). The organic phase in the cooled reaction solution was extracted with dichloromethane (300 mL) through a separatory funnel and washed with 1M hydrochloric acid (50 mL) and water (200 mL×2). The dichloromethane in the obtained organic phase was removed by an evaporator, and then the unreacted 1,6-dichlorohexane was removed at 90°C under reduced pressure. The obtained residue was hung on a silica gel column (developing solvent: hexane: chloroform = 9:1) to obtain the following compound I (13.6 mmol).

[0295]

Chemical formula 22

[0296]

[0297] (2) Synthesis of polymer I-Cl

[0298] Compound I (2 mmol), cesium carbonate (6 mmol), pivalic acid (2 mmol), tri(2-methoxyphenyl)phosphine (14 mg) and Pd2(dba)3·CHCl3 complex (10.4 mg) were added to a two-necked flask, and then dehydrated tetrahydrofuran (3 mL) was added and stirred under nitrogen. Next, the prepared solution was added to the two-necked flask via a syringe in a manner that minimizes the entry of air. The prepared solution was prepared by dissolving tetrafluorophenylene (2.06 mmol) in tetrahydrofuran (1 mL). The mixed solution was reacted under nitrogen at room temperature (25°C) for 45 minutes, and then at 95°C for 24 hours.

[0299] 1M hydrochloric acid and chloroform were added to the obtained reactant (solid component), and after stirring at 40°C for 12 hours, the organic phase was extracted by a separatory funnel. After washing the extracted organic phase with water, the liquid component in the obtained organic phase was removed by an evaporator, and it was dried and solidified. The obtained residue was dissolved in chloroform and precipitated again in methanol. The obtained precipitate was filtered, and the solid component was washed with hexane during the process of removing the liquid component. Then, the obtained solid component was vacuum dried to obtain the following polymer I-Cl.

[0300]

Chemical formula 23

[0301]

[0302] (3) Synthesis of PFT-C10-TMA

[0303] Polymer I-Cl (200 mg) was dissolved in chlorobenzene (20 mL). A 25% by mass trimethylamine methanol solution (2 mL) was added to the obtained solution, and the mixture was stirred at 105°C for 6 hours. Then, dimethyl sulfoxide (10 mL) was added and stirred for another 6 hours. After most of the chlorobenzene in the reaction solution was removed by an evaporator, dimethyl sulfoxide (20 mL) and a 25% by mass trimethylamine methanol solution (3 mL) were added, and the reaction was stirred at 100°C for 3 hours to terminate the reaction. At 80°C, dimethyl sulfoxide in the obtained reaction solution was removed by an evaporator, and the mixture was dried and solidified. Water was added to the dried and solidified residue, and the mixture was filtered. Water was added to the obtained solid component, and the mixture was stirred at 80°C. Then, the following polymer PFT-C10-TMA (203 mg) was obtained by cooling to room temperature (25°C), filtering, and vacuum drying the obtained solid component.

[0304]

Chemical formula 24

[0305]

[0306] [Manufacturing Example 2: Manufacture of anode catalyst]

[0307] Commercially available nickel foam was uniformly pressed into a thickness of 200 nm. The nickel foam was acid-treated with HCl and washed with ethanol and water. Next, the nickel foam was immersed in 1M KOH and a 10 cm 2 A nickel foam counter electrode and a Hg / HgO reference electrode were applied with 2.5 V vs RHE for 1 minute to oxidize the surface of the nickel foam to form a nickel oxide layer containing NiOOH, thereby obtaining an intermediate product.

[0308] The intermediate product was immersed in the following electrolyte: containing 25 mM Fe 2+ , (NH4)2SO4, H2SO4 and water, the pH was adjusted to below 3, the electrolyte was degassed with N2, and Fe was electrodeposited by chronoamperometry using a Pt counter electrode and an Ag / AgCl reference electrode to obtain a Ni-OOH-Fe-Ni foam catalyst with a thickness of about 250nm.

[0309] [Manufacturing Example 3: Manufacture of cathode catalyst]

[0310] About 0.2 mg of RuCl3 was dissolved in 50 ml of deionized water to prepare a Ru ion solution. The acid-treated nickel foam was immersed in the Ru ion solution and kept for 24 hours to allow electrochemical replacement of Ni ions and Ru ions on the substrate surface. After impregnation, the nickel foam was atmospherically dried to obtain a Ru-modified substrate. High-purity nitrogen was flowed into the furnace at a flow rate of 60 SCCM, and sodium hypophosphite was arranged on the upstream side of the furnace, and the Ru-modified substrate was arranged on the downstream side. The temperature was raised at a rate of 3°C / min, maintained at 350°C for 4 hours and phosphated to obtain a NiRu2P-Ni foam catalyst.

[0311] [Example 1: Preparation of pore-filled membrane]

[0312] A solution was prepared in which the anion exchange polymer PFT-C10-TMA obtained in Preparation Example 1 was dissolved. In addition, as a porous substrate, an ultra-high molecular weight polyethylene porous substrate having a porosity of 46% and a thickness of 25 μm was prepared. After the solution was infiltrated into the porous substrate, the solvent was removed to prepare a pore-filled membrane filled with PFT-C10-TMA.

[0313] The filling of the anion exchange polymer PFT-C10-TMA in the pores was confirmed by Raman analysis. Fig. 7A and Figure 7B shown. Fig. 7A The Raman spectra of the polyethylene porous substrate, the filled polymer (PFT-C10-TMA), and the pore-filled membrane (depth 12 μm) are shown in order from the top layer. Through these comparisons, as shown in the figure, at the depth of 12 μm in the pore-filled membrane, both the spectrum from the substrate and the spectrum from the polymer are detected, which shows that the porous substrate is filled with polymer. In addition, Figure 7B is the Raman spectrum in the depth direction of the pore-filled film. Figure 7B As shown, a spectrum derived from the polymer is detected at any measurement point, which shows that the polymer is filled almost uniformly in the depth direction of the porous substrate.

[0314] [Example 2: Preparation of pore-filled membrane]

[0315] A pore-filled membrane was prepared in the same manner as in Example 1 except that the porous substrate in Example 1 was changed to a polytetrafluoroethylene (PTFE) porous substrate having a porosity of 70% and a thickness of 25 μm. Raman analysis was performed in the same manner as in Example 1 to confirm that the porous substrate was also filled with the polymer.

[0316] [Comparative Example 1: Preparation of pore-filled film]

[0317] A pore-filled membrane was prepared in the same manner as in Example 1 except that the porous substrate in Example 1 was changed to a polyimide porous substrate with a porosity of 60% and a thickness of 20 μm. Raman analysis was performed in the same manner as in Example 1, and the results showed that the porous substrate could not be filled with a polymer.

[0318] <Water electrolysis test>

[0319] The pore-filled membrane of Example 2 was used as the electrolyte membrane, the Ni-OOH-Fe-Ni foam catalyst of Manufacturing Example 2 was used as the anode catalyst, and the NiRu2P-Ni foam catalyst of Manufacturing Example 3 was used as the cathode catalyst to produce a membrane electrode assembly. A 1M KOH aqueous solution was flowed into both sides of the anode and cathode, and the temperature was set at 80°C to conduct a water electrolysis test. The test results are shown in FIG. Figure 6 As shown. Figure 6 As shown, it can be seen that the water electrolysis device using the pore-filled membrane of Example 1 can perform water electrolysis with high efficiency.

[0320] As described above, the present pore-filled film has the following characteristics.

[0321] The present pore-filled membrane in which the pores of the porous substrate are filled with a polyarylene polymer has excellent mechanical strength and chemical durability equal to or higher than that of a membrane formed with a polyarylene polymer. By using a polyarylene polymer having a structural unit represented by the general formula (1), a pore-filled membrane having excellent ion conductivity can be obtained. By using a polyolefin-based porous substrate, the chemical durability is further improved, and the polyarylene polymer is easily filled into the pores. By using such a pore-filled membrane, a fuel cell and an electrolysis device having excellent durability can be obtained.

[0322] This application claims priority and benefits based on Japanese patent application No. 2022-082500, filed on May 19, 2022, the entire contents of which are incorporated by reference into this application.

[0323] Description of Reference Numerals

[0324] 1: water electrolysis device, 5: electrolyte membrane (pore filling membrane), 6: cell, 7: power supply, 8: membrane electrode assembly, 10: anode (anode electrode), 11: anode catalyst, 12: first diffusion layer, 13: separator, 14: gas flow path, 20: cathode (cathode electrode), 21: cathode catalyst, 22: second diffusion layer, 23: separator, 24: gas flow path, 30, 40: anode catalyst, 31, 41: nickel foam, 32: nickel oxide layer, 33: NiF containing e layer, 42: phosphide layer, 50: cathode catalyst, 51: porous body of metal or metal alloy, 52: layer containing Ru and metal phosphide, 60: fuel cell, 65: electrolyte membrane (pore filling membrane), 66: cell, 67: external circuit, 68: membrane electrode assembly, 70: anode unit, 71: anode catalyst layer, 72: diffusion layer, 73: separator, 74: gas flow path, 80: cathode unit, 81: cathode catalyst layer, 83: separator, 84: gas flow path

Claims

1. A pore-filling membrane, wherein: Having a porous substrate and a polyarylene polymer, The polyarylene polymer is filled in the pores of the porous substrate.

2. The pore-filling membrane according to claim 1, wherein: The polyarylene polymer has a structural unit represented by the following general formula (1): 【Chemical formula 1】 in, Ar 1 It is an aromatic group having an ion exchange group, or a group formed by connecting aromatic rings having an ion exchange group through a single bond. 1 Can be the same or different, Ar 2 is an aromatic group having no ion exchange group, or a group in which two or more aromatic rings having no ion exchange group are connected by a single bond or a spiro atom, and a plurality of Ar 2 Can be the same or different, Ar 1 The aromatic ring and Ar 2 The aromatic rings are connected by single bonds.

3. The pore-filling membrane according to claim 1 or 2, wherein: The porous substrate is a polyolefin-based porous substrate.

4. The pore-filling film according to claim 3, wherein: The polyolefin-based porous substrate is a polyethylene porous substrate, a polypropylene porous substrate, or a polytetrafluoroethylene porous substrate.

5. A fuel cell, wherein: A pore-filled membrane according to claim 1 or 2.

6. An electrolysis device, wherein: A pore-filled membrane according to claim 1 or 2.

Citation Information

Patent Citations

  • Polymer, electrolyte membrane, and solid polymer fuel cell

    JP2018135487A

  • Polymer, precursor, method for producing polymer, electrolyte membrane, fuel cell, water electrolysis and electrolysis technique

    JP2021042351A

  • Pressure detection circuit, device, and pressure input device

    JP2022082500A